A randomised controlled trial of self-help interventions in patients with a primary care diagnosis of irritable bowel syndrome. Issue 5 (12th August 2005) - Robinson, A; Lee, V; Kennedy, A; Middleton, L; Rogers, A; Thompson, D G; Reeves, D
Abstract : Introduction: Functional abdominal symptoms are very common and account for nearly two million primary care consultations in Britain every year and produce significant morbidity. The aims of this study were to evaluate the impact of two self-help interventions on consultation rates and symptom severity in patients with a primary care diagnosis of irritable bowel syndrome. Methods: A total of 420 patients from 54 primary care centres were randomised either to receive self-help information in the form of a guidebook or the guidebook plus a "self-help" group meeting or to be in a control group receiving neither intervention. Data were collected using questionnaires and primary care records. Results: At one year, patients in the guidebook group had a 60% reduction in primary care consultations (p<0.001) and a reduction in perceived symptom severity (p<0.001) compared with controls. Allocation to the self-help group conferred no additional benefit. Actual symptom scores did not change significantly in any group. Costs per patient were reduced by £73 (confidence interval £43, £103) or 40% per year. Conclusion: Introduction of a self-help guidebook results in a reduction in primary care consultations, a perceived reduction in symptoms, and significant health service savings. This suggests that patients attending their primary care physician with functional abdominal symptoms should be offered self-help information as part of their management.